Author’s Meta-reflection in the Poetry of Boris Ryzhy - Zyryanov, Оleg V. (Izvestiâ Uralʹskogo federalʹnogo universiteta. Seriâ 2, Gumanitarnye nauki, 2025)
This article is a preliminary study of the complex and challenging area of the creative personality of the poet Boris Ryzhy. It focuses on a notable aspect of this exceptional creative individuality: the author’s meta-reflection in the poet’s texts. The purpose of the article is to examine the author’s metatext of Ryzhy’s poetry, as well as all its components, taken separately or as a complex, sometimes even in a systemic and integral unity. The research methods employed are structural-typological, incorporating a holistic analysis of a distinct lyrical work. The research challenges the prevailing notion of poet Ryzhy as an exclusively spontaneous and emotional individual. The creative personality of this soulful lyric poet is characterised by professional sophistication in matters of verse poetics proper, which found expression in a complex system of meta-elements, such as dedications and epigraphs, literary intertextuality, and examples of genre and verse meta-reflection. Ryzhy’s lyrical poetry includes a significant number of poetological poems. They focus on the author’s process of creating poetry, offering a direct insight into the poet’s thought process. The poem I am Cold, Reader, and It Feels Dark... is selected as the most representative text. It is analysed in a comparative-contrastive manner against the well-known precedent text by E. Boratynsky, My Talent is Poor, My Voice Has Little Weight... It is demonstrated that in his creative dialogue with the previous poetic tradition, Ryzhy not only preserves the personal autonomy of his poetic personality but also accumulates its creative potential to the full.